Pengembangan Media Pembelajaran Power Point Ispring Presenter Pada Materi Kosakata Bahasa Arab Peserta Didik Kelas V MI Tarbiyatul Athfal Lampung Timur - Guntur; Amiruddin; Nisaul Jamilah (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2019)
Using media in language teaching has various weaknesses in terms of design, material aspects, and in terms of language. Based on this, the problem of this research